The depth of penetration of the electric field induced by a surface acoustic wave in a piezoelectric semiconductor system - CEROWSKI, Zenon (Archives of Acoustics, 1981)
This paper presents calculations of the penetration depth of the electric field accompanying an acoustic wave for penetration into a semiconductor layer over the plane of propagation when a dc electric field is applied to the piezoelectric – semiconductor system perpendicular to the propagation direction of the wave.